A method of telemetering chronometric radiosonde data Through rawin channel - MATHUR, L S.; DHAR, N. C.; BHATTACHARYA, H.S. (MAUSAM, 1956)
The paper describes a method of telemetering chronometric radiosonde data on the F-M channel of the receiver of the radio theodolite. A squegging oscillator is used in conjunction with the chronometric radiosonde to obtain F-M signals from the 400 Mcs rawin transmitter at each contact of the meteorologically sencitive pens with the contacting helix of the radiosonde. With the ground-based rawin receiver an auxiliary electronic unit is used to work the radiosonde recorder, whenever the F-M signals are picked up by the radio-theodolite receiver. The details of the balloon borne unit and auxiliary equipment are also described.